Hospitality e-marketing
"This fully revised edition shows how to apply the principles of marketing within the hospitality industry. Covers e-marketing strategies for all types of hospitality businesses. With concise explanations and detailed illustrations, this edition includes extensive revisions of the material on the impact that the internet has had on both marketing and hospitality." --